Nutrition and the psychoneuroimmunology of postpartum depression - Ellsworth-Bowers, E. R. (2012)
Postpartum depression (PPD) is a relatively common and often severe mood disorder that develops in women after childbirth. The aetiology of PPD is unclear, although there is emerging evidence to suggest a psychoneuroimmune connection. Additionally, deficiencies in n-3 PUFA, B vitamins, vitamin D and trace minerals have been implicated. This paper reviews evidence for a link between micronutrient status and PPD, analysing the potential contribution of each micronutrient to psychoneuroimmunological mechanisms of PPD. Articles related to PPD and women’s levels of n-3 PUFA, B vitamins, vitamin D and the trace minerals Zn and Se were reviewed. Findings suggest that while n-3 PUFA levels have been shown to vary inversely with PPD and link with psychoneuroimmunology, there is mixed evidence regarding the ability of n-3 PUFA to prevent or treat PPD. B vitamin status is not clearly linked to PPD, even though it seems to vary inversely with depression in non-perinatal populations and may have an impact on immunity. Vitamin D and the trace minerals Zn and Se are linked to PPD and psychoneuroimmunology by intriguing, but small, studies. Overall, evidence suggests that certain micronutrient deficiencies contribute to the development of PPD, possibly through psychoneuroimmunological mechanisms. Developing a better understanding of these mechanisms is important for guiding future research, clinical practice and health education regarding PPD.